Effect of Opioid Free Anesthesia versus Opioid-Balanced Anesthesia on Systemic Inflammatory Responses for Elective Oncologic Abdominal Surgeries in Suez Canal University Hospitals: A Comparative Randomized Clinical Trial - Amr Mohamed Sabry, Alaa El-Din Mohamed El-kassaby, Salah Abd-ElFattah M. Ismail, Emad El-dien Ahmed, Ahmed Ahmed El-lilly (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Opioids administration consequences are neither scarce nor benign for the patient. The aim of the present study was to improve the systemic inflammatory stress responses and functional outcomes in the patients undergoing elective oncologic abdominal surgery. Patients and methods: This prospective clinical trial included 60 patients undergoing elective oncologic abdominal surgery. Patients were equal divided to Opioid Based Anesthesia (OBA) group, and Opioid Free Anesthesia (OFA) group. Each participant was subjected to medical history, physical examination, anesthetic assessments, and laboratory investigations. Results: Both groups were well matched as regard sex and age with no statistically significant difference between them. However, the weight of the OFA patients was significantly higher than that of the OBA group. HR and MBP were significantly lower in the OFA group than OBA group at 90 and 120 minutes after induction, at the end of surgery, at extubation, as well as one hour and two hours after surgery. CRP level was significantly lower in the OFA group than in the OBA group at 2 and 24 hours after surgery periods. TLC levels were significantly lower in the OFA group than in the OBA group at 24 hours after surgery. Conclusion: OFA is beneficial and effective than OBA. OFA could be recommended in the patients undergoing elective oncologic abdominal surgeries.